Development of an Interactive E-Module Based on Project-Based Learning to Improve English Speaking Skills for Seventh Grade Junior High School Students - Dwi Mahya Sari; Dina Martha Fitri; Rangga Firdaus; Sheren Dwi Oktaria; Herpratiwi (Universitas Islam Negeri Palopo, 2025)
This article presents the development of an interactive e-module based on Project-Based Learning (PBL) aimed at enhancing English speaking skills for Grade VII students of Junior High School (SMP). Speaking skills are critical for students in the 21st century, and traditional print-based modules often fail to provide opportunities for meaningful interaction. This research employs a research and development (R&D) approach with the 4D model (Define, Design, Develop, Disseminate). The needs of students were analyzed during the Define phase, while content, project tasks, and interactive media were designed during the Design phase. The module was developed using a digital platform and integrated with the PBL cycle, allowing students to engage in authentic projects such as vlogs, drama, interviews, and presentations. Expert validation showed that the designed e-module is feasible for use; practitioners and students found it practical and effective (Amini, 2022). PBL has proven to enhance motivation, self-confidence, creativity, and speaking fluency (Luh et al., 2017), thus the integration of PBL in the e-module is expected to encourage active student participation.